The Volatility Assessment of CO2 Emissions in Uzbekistan: ARCH/GARCH Models - Kuziboev, Bekhzod; Vysušilová, Petra; Salahodjaev, Raufhon; Rajabov, Alibek; Rakhimov, Tukhtabek (International Journal of Energy Economics and Policy, 2023)
The study is pioneer to investigate the volatility of CO2 emissions in Uzbekistan. To this end, ARCH (Autoregressive Conditional Heteroskedasticity) and GARCH (Generalized Autoregressive Conditional Heteroskedasticity) models are used spanning the period 1925-2021 for the annual data of CO2 emissions. The results indicate that ARCH model is more adequate that GARCH model in the volatility assessment. Furthermore, it is found that the volatility of CO2 emissions in Uzbekistan is very high. The policymakers have to consider the high volatility of CO2 emissions in the environmental policy measures dedicated to reduce carbon dioxide emissions.